Evaluation of the efficacy and safety of Tribulus terrestris in male sexual dysfunction—A prospective, randomized, double-blind, placebo-controlled clinical trial. (May 2017) - Kamenov, Zdravko; Fileva, Svetlana; Kalinov, Krassimir; Jannini, Emmanuele A.
Highlights: Extracts of the plant Tribulus terrestris significantly improve erectile function. In this randomized placebo-controlled trial, a significant improvement was seen in overall sexual function among those treated with an extract of Tribulus terrestris . No drug-related serious adverse events were observed. Abstract: Objective: The primary objectives were to compare the efficacy of extracts of the plant Tribulus terrestris (TT; marketed as Tribestan), in comparison with placebo, for the treatment of men with erectile dysfunction (ED) and with or without hypoactive sexual desire disorder (HSDD), as well as to monitor the safety profile of the drug. The secondary objective was to evaluate the level of lipids in blood during treatment. Participants and design: Phase IV, prospective, randomized, double-blind, placebo-controlled clinical trial in parallel groups. This study included 180 males aged between 18 and 65 years with mild or moderate ED and with or without HSDD: 90 were randomized to TT and 90 to placebo. Patients with ED and hypertension, diabetes mellitus, and metabolic syndrome were included in the study. In the trial, an herbal medicine intervention of Bulgarian origin was used (Tribestan ®, Sopharma AD). Each Tribestan film-coated tablet contains the active substance Tribulus terrestris, herba extractum siccum (35–45:1) 250 mg which is standardized to furostanol saponins (not less than 112.5 mg). Each patient received orally 3 × 2 film-coated tablets daily after meals, during the 12-week treatment period. At the end of each month, participants' sexual function, including ED, was assessed by International Index of Erectile Function (IIEF) Questionnaire and Global Efficacy Question (GEQ). Several biochemical parameters were also determined. The primary outcome measure was the change in IIEF score after 12 weeks of treatment. Complete randomization (random sorting using maximum allowable% deviation) with an equal number of patients in each sequence was used. This randomization algorithm has the restriction that unequal treatment allocation is not allowed; that is, all groups must have the same target sample size. Patients, investigational staff, and data collectors were blinded to treatment. All outcome assessors were also blinded to group allocation. Results: 86 patients in each group completed the study. The IIEF score improved significantly in the TT group compared with the placebo group (Р < 0.0001). For intention-to-treat (ITT) there was a statistically significant difference in change from baseline of IIEF scores. The difference between TT and placebo was 2.70 (95% CI 1.40, 4.01) for the ITT population. A statistically significant difference between TT and placebo was found for Intercourse Satisfaction (p = 0.0005), Orgasmic Function (p = 0.0325), Sexual Desire (p = 0.0038), Overall Satisfaction (p = 0.0028) as well as in GEQ responses (p < 0.0001), in favour of TT. There were no differences in the incidence of adverse events (AEs) between the two groups and the therapy was well tolerated. There were no drug-related serious AEs. Following the 12-week treatment period, significant improvement in sexual function was observed with TT compared with placebo in men with mild to moderate ED. TT was generally well tolerated for the treatment of ED.